The Effect of Resistance Training on Performance of Gross Motor Skills and Balance in Children with Spastic Cerebral Palsy - Ebrahim Zarrinkalam; Majid Ebadi Fara (Biyumikānīk-i varzishī)
Objective: Cerebral palsy is the most common chronic motor disability in children and can have negative effect on motor functions. The purpose of this study was to investigate the effect of eight weeks resistance training on gross motor ability, balance and walking speed in a group of such children.